PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PENDIDIKAN EKONOMI DENGAN MODEL PROBLEM-BASED LEARNING BERBANTUAN SIMULASI DILEMA ETIKA BISNIS - Yusuf Yusuf; Tansini Tansini; Fitriani S Fitriani; Ambo Rappe (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Critical thinking is an essential competency for Economics Education students to analyze problems, evaluate alternative solutions, and make sound decisions when facing complex business ethics dilemmas. However, preliminary observations revealed that students' critical thinking skills in the Business Ethics course were still inadequate, particularly in connecting theoretical concepts with the resolution of authentic business cases. This study aimed to examine the improvement of students' critical thinking skills through the implementation of the Problem-Based Learning (PBL) model supported by business ethics dilemma simulations. The study employed a quantitative approach using a quasi-experimental design. The participants consisted of 41 Economics Education students enrolled in the Business Ethics course. Data were collected using a critical thinking skills test comprising ten essay questions based on business ethics cases and an observation sheet assessing students' critical thinking performance. The data were analyzed using descriptive and inferential statistical techniques to determine changes in students' critical thinking skills following the implementation of the learning model. The findings indicate that the implementation of Problem-Based Learning assisted by business ethics dilemma simulations significantly improved students' critical thinking skills across all measured indicators. These results suggest that integrating problem-based learning with contextual simulation activities provides more meaningful learning experiences, promotes active student engagement, and strengthens analytical as well as ethical decision-making abilities. Therefore, this instructional model can serve as an innovative alternative for enhancing the quality of Business Ethics learning in higher education. ABSTRAK Kemampuan berpikir kritis merupakan kompetensi esensial yang perlu dimiliki mahasiswa Pendidikan Ekonomi untuk menganalisis persoalan, mengevaluasi berbagai alternatif, serta mengambil keputusan yang tepat dalam menghadapi dilema etika bisnis. Namun, hasil studi pendahuluan menunjukkan bahwa kemampuan berpikir kritis mahasiswa pada mata kuliah Etika Bisnis masih belum optimal, terutama dalam menghubungkan konsep teoretis dengan penyelesaian kasus nyata. Penelitian ini bertujuan menganalisis peningkatan kemampuan berpikir kritis mahasiswa melalui penerapan model Problem-Based Learning (PBL) berbantuan simulasi dilema etika bisnis. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi-experimental. Sampel penelitian berjumlah 41 mahasiswa Program Studi Pendidikan Ekonomi yang menempuh mata kuliah Etika Bisnis. Data dikumpulkan melalui tes kemampuan berpikir kritis berupa sepuluh soal esai berbasis kasus etika bisnis dan lembar observasi aktivitas berpikir kritis. Analisis data dilakukan menggunakan statistik deskriptif dan inferensial untuk menguji perubahan kemampuan berpikir kritis setelah penerapan model pembelajaran. Hasil penelitian menunjukkan bahwa penerapan model Problem-Based Learning berbantuan simulasi dilema etika bisnis mampu meningkatkan kemampuan berpikir kritis mahasiswa secara signifikan pada berbagai indikator yang diukur. Temuan ini mengindikasikan bahwa integrasi pembelajaran berbasis masalah dengan simulasi kontekstual memberikan pengalaman belajar yang lebih bermakna, meningkatkan partisipasi aktif mahasiswa, serta memperkuat kemampuan analisis dan pengambilan keputusan etis. Dengan demikian, model pembelajaran ini layak dijadikan alternatif inovasi pembelajaran untuk meningkatkan kualitas pembelajaran Etika Bisnis di perguruan tinggi.